The Readiness of The Measuring Model of Infrastructure Provisioning Under Sharia Public-Private Partnerships Financing Scheme - Santoso, Sugeng; Siswanti, Indra; Nurhidajat, R.; Isa, Salmi Mohd; Marfatah, Muhammad Ramadhani (IQTISHODUNA: Jurnal Ekonomi Islam, 2022)
Meeting the demands of infrastructure development is reliant on contributions from different parties, including government bodies and businesses. To fulfill this crucial goal, a financing scheme needs to be established, promoting collaboration among these stakeholders. This scheme enables effective contributions from both government and business entities. As the most populous Muslim country in the world, Indonesia is undergoing rapid advancements within the halal value chain, which includes the initiation of infrastructure provisioning through the Sharia-compliant Public-Private Partnerships (PPP) financing scheme. Therefore, this research assessed the Innovation Readiness Level (IRL) and Technology Readiness Level (TRL).  Employing a participatory approach through Focus Group Discussions (FGD), stakeholder dialogues were conducted to explore transportation infrastructure financing under the Sharia PPP scheme. The analysis gauged readiness levels using self-assessment for IRL and TRL, subsequently corroborated by respondents to ascertain their preparedness. This research yielded an analytical model to measure infrastructure financing readiness under the Sharia PPP scheme. The results indicated IRL 1, accompanied by a TRL 3. This showed the necessity of refining the readiness assessment model to enhance stakeholder comprehension of associated advantages. Ideally, IRL could be raised beyond 1, and achieving Katsinov 3 alongside TRL levels of 8 or 9 would greatly instill confidence among relevant stakeholders considering the adoption of the Sharia PPP financing scheme.